2006
DOI: 10.1007/s00253-005-0185-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the urease gene of Agaricus bisporus: a tool for studying fruit body formation and post-harvest development

Abstract: Fruit body initials of Agaricus bisporus contain high levels of urea, which decrease in the following developmental stages until stage 4 (harvest) when urea levels increase again. At storage, the high urea content may affect the quality of the mushroom, i.e. by the formation of ammonia from urea through the action of urease (EC 3.5.1.5). Despite the abundance of urea in the edible mushroom A. bisporus, little is known about its physiological role. The urease gene of A. bisporus and its promoter region were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Ureases of bacteria, fungi and higher plants are highly conserved 44 . In higher plants and fungi, the enzyme is encoded by a single gene 45, 46. Thus, our results showed that the poure transcript of DK13 × 3 was from the MK13 poure gene and that RNA editing also occurred (Table 6).…”
Section: Resultsmentioning
confidence: 61%
“…Ureases of bacteria, fungi and higher plants are highly conserved 44 . In higher plants and fungi, the enzyme is encoded by a single gene 45, 46. Thus, our results showed that the poure transcript of DK13 × 3 was from the MK13 poure gene and that RNA editing also occurred (Table 6).…”
Section: Resultsmentioning
confidence: 61%
“…This finding once again confirms that higher fungi of the family Agaricaceae accumulate substantial amounts of urea in their fruiting bodies [ 8 ]. It has been suggested that urea acts as an osmotically favourable nitrogen reserve for fungi [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exceptionally, some metabolites including urea, glycerol, acetyl-glucosamine, and hepsiziprenols were differentially expressed in the different parts of beech mushrooms. Biochemically, urea is formed by purine degradation in ornithine cycle and functions the translocation of water and nutrients required for fruiting body development [33]. Wagemaker et al (2006) reported the higher urease expression in stipe portion which gradually decrease during the later stages of mushroom development [34].…”
Section: Discussionmentioning
confidence: 99%